2017
DOI: 10.2337/db16-1232
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Specific Deficiency of De Novo Sphingolipid Biosynthesis Leads to Lipodystrophy and Insulin Resistance

Abstract: Sphingolipids have been implicated in the etiology of chronic metabolic diseases. Here, we investigated whether sphingolipid biosynthesis is associated with the development of adipose tissues and metabolic diseases. SPTLC2, a subunit of serine palmitoyltransferase, was transcriptionally upregulated in the adipose tissues of obese mice and in differentiating adipocytes. Adipocyte-specific SPTLC2-deficient (aSPTLC2 KO) mice had markedly reduced adipose tissue mass. Fatty acids that were destined for the adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
(57 reference statements)
3
38
0
Order By: Relevance
“…Alexaki et al [48] showed that adipocyte-specific Sptlc1-knockout mice exhibit insulin resistance with agedependent loss of adipose tissue, increased macrophage infiltration and tissue fibrosis. Furthermore, Lee et al [49] showed that adipocyte-specific Sptlc2-knockout mice display systemic insulin resistance and hyperglycaemia. Taken together with our observations, chronic sphingolipid metabolism downregulation could thus potentially interfere with liver, muscle, adipose and beta cell function, contributing to type 2 diabetes onset.…”
Section: Discussionmentioning
confidence: 99%
“…Alexaki et al [48] showed that adipocyte-specific Sptlc1-knockout mice exhibit insulin resistance with agedependent loss of adipose tissue, increased macrophage infiltration and tissue fibrosis. Furthermore, Lee et al [49] showed that adipocyte-specific Sptlc2-knockout mice display systemic insulin resistance and hyperglycaemia. Taken together with our observations, chronic sphingolipid metabolism downregulation could thus potentially interfere with liver, muscle, adipose and beta cell function, contributing to type 2 diabetes onset.…”
Section: Discussionmentioning
confidence: 99%
“…Fbp2 deletion did not alter glucose metabolism during the feeding condition Because energy expenditure showed a different pattern between feeding and fasting periods, we further tested whether Fbp2 deficiency alters glucose metabolism in the fed condition. To measure in vivo whole-body and tissuespecific glucose fluxes under feeding-mimicking conditions where insulin and exogenous glucose are supplied, we performed hyperinsulinemic-euglycemic clamp studies on WT and Fbp2 KO mice as previously reported 23,30 . There was no difference in insulin-stimulated whole-body glucose utilization between Fbp2 KO and WT mice, as reflected by the identical glucose infusion rates needed to maintain euglycemia during the steady state ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CER and SM, which are included as part of sphingolipids, have been demonstrated to play a substantial role in the development of a variety of diseases as important bioactive mediators. In adipose tissue, adipocyte-specific ablation of SPTLC2, a subunit of serine palmitoyltransferase that is an initial enzyme in sphingolipid biosynthesis, has been reported to increase CER[C24:1] content in adipose tissue of HFD-fed mice, and reduce adipose tissue mass with marked Pck1 downregulation 44 . In addition, the adipocyte-specific SPTLC2-knockout mice also accompanied hepatic steatosis, implying a mirror image phenotype of lipid deposition and content as the Ipra-treated mice in our study.…”
Section: Discussionmentioning
confidence: 99%